پنجاب پولیس کاتعارف، اختیارات اور ذمہ داریاں : اسلامی تعلیمات کی روشنی میں ایک مطالعہIntroduction, Authorities and Responsibilities of Punjab Police: A Study in the light of Islamic Teachings (Al-Qamar, 2022)
Islam is a comprehensive, universal, compatible with the requirements of the conditions of every era and a benevolent religion of humanity. In this religion, there are laws related to all areas of life, by following the laws, a person can live a peaceful life. Also, unrest and chaos spreads in the society when the importance of law disappears in the hearts of the people and they consider it their privilege to oppress the weak people with the force of power and this is the biggest reason for the deterioration in the society.                                                                                                                In the religion of Islam, in order to maintain social stability and to live a peaceful life, all the basic rights have been given to every human being, thanks to which his religion, intellect, wealth, life and honor are protected. This clearly shows that Islam wants to protect human rights in every case. This is the reason why Islam supports every measure to ensure the protection of human rights. Security institutions are of great importance for maintaining peace and order in the society and for the protection of human property is pregnant. After the migration to Medina, Messenger of Allah (SAW) made security arrangements to protect the lives and property of the Muslims and the people of Medina. This security took the form of a formal department which was named as police. The main task of this institution is to maintain law and order in the society and to protect people's lives and property. If seen in the context of Pakistani society, the police of our country. The police of the largest province are called the Punjab Police. In this article, the Punjab Police will be discussed. And at the same time, its structure and responsibilities in the light of Islamic teachings. And options will be explained in detail.
Keywords: Punjab Police; Universal; Laws; Department; Protection; Peace.; Human rights; Society; Security; Stability